Knowledge Regarding Pedestrian Injury Prevention among Secondary School Going Children Of Karachi, Pakistan - Anum Arshad Beg, Anum Arshad Beg; Marie Andrades, Marie Andrades; Zainab Muhammad Anjarwala, Zainab Muhammad Anjarwala; Veena Kumari Karmani, Veena Kumari Karmani (Journal of Rawalpindi Medical College, 2020)
BACKGROUND: Pedestrian injuries are a major public health problem, especially among children, in developing countries. In Pakistan, however, children’s knowledge regarding this issue has not been addressed. The objective of the study was to determine the magnitude of knowledge regarding pedestrian injury prevention among children studying in secondary schools of Saddar Town, Karachi. METHODS: It was a cross-sectional study, conducted in six secondary schools of Saddar Town Karachi, for a period of six months from October 2012 to March 2013. A total of 470 secondary school children (grades 8-10), were selected through a two stage stratified random sampling, across 6 schools in Saddar Town, Karachi. A pilot-tested questionnaire developed on published literature and road safety rules, assessed children’s knowledge about safe road crossing, walking and playing on roads. Data was analyzed using SPSS version 19, applying logistic regression analysis. RESULTS: There were 46.8% boys and 53.2% girls, majority 12 to 15 years of age (69.1%). Overall knowledge was adequate (68.9% versus 31.1%), boys (52.2%) versus girls (47.8%). 16.6% children had inadequate knowledge about road crossing, 33.6% about walking and 8.7% about playing on roads. Factors significantly associated with inadequate knowledge were younger age (OR=2.8, 95%CI=0.8-5.1, p value=0.04), male gender (OR=2.08, 95% CI=1.35-3.21) and walking to school (OR=7.5, 95%CI=2.6-32.8). CONCLUSION: This study indicates that 31% children have inadequate knowledge regarding pedestrian injury prevention, a significant proportion of a vulnerable population. However, due to limited sample size, not addressing temporality, larger studies assessing road behaviors of children are required.